Answer:
(6, - 1 )
Explanation:
Given the 2 equations
x + 7y = - 1 → (1)
- 4x - 2y = - 22 → (2)
Rearrange (1) expressing x in terms of y by subtracting 7y from both sides
x = - 1 - 7y → (3)
Substitute x = - 1 - 7y into (2)
- 4(- 1 - 7y) - 2y = - 22 ← distribute and simplify left side
4 + 28y - 2y = - 22
4 + 26y = - 22 ( subtract 4 from both sides )
26y = - 26 ( divide both sides by 26 )
y = - 1
Substitute y = - 1 into (3) for corresponding value of x
x = - 1 - 7(- 1) = - 1 + 7 = 6
Solution is (6, - 1 )